2007
DOI: 10.1039/b613835g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urinary tellurium metabolite in rats administered sodium tellurite

Abstract: Tellurium (Te) is one of the important metalloids used in industry, and is ubiquitously found in the environment. However, the biological and toxicological effects of Te are still unclear despite its being recognized as a hazardous element. In this study, we attempted to identify urinary Te metabolites (UTMs) in rats by HPLC-ICP-MS and electrospray ionization (ESI)-MS. To unambiguously identify UTMs, two different chromatographic mechanisms, i.e., multi-mode gel filtration and cation exchange columns, were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…the literature for speciation of tellurium is shown in Table 4. As could be seen, the LODs of this method are much lower than those obtained by SPE-HG-AAS [32], SPE-ICP-MS [12], SPE-ICP-AFS [9], LLE-AAS [1], CE-UV [33], and HPLC-ICP-MS [4].…”
Section: Analytical Performancementioning
confidence: 70%
See 1 more Smart Citation
“…the literature for speciation of tellurium is shown in Table 4. As could be seen, the LODs of this method are much lower than those obtained by SPE-HG-AAS [32], SPE-ICP-MS [12], SPE-ICP-AFS [9], LLE-AAS [1], CE-UV [33], and HPLC-ICP-MS [4].…”
Section: Analytical Performancementioning
confidence: 70%
“…Recently, Te, as an alloy with germanium (Ge) and antimony (Sb), has found use in digital versatile disk-random access memory (DVD-RAM) and DVDrecordable disks (DVD-RW) [1]. Thus, these metalloids are expected to be widely used in everyday life as storage media.…”
Section: Introductionmentioning
confidence: 99%
“…Te was preferably distributed to the lungs and spleen. It is reported that Te was metabolized by methylation, and the resulting TMTe was excreted into urine (Ogra et al, 2007). As a metabolic intermediate, volatile dimethyltelluride could be formed and the lungs seemed to accumulate the volatile metabolite (DeMeio and Jetter, 1948).…”
Section: Distribution Of Metalloids To Organs and Blood Cellsmentioning
confidence: 99%
“…22 Other chromatographic mechanisms, such as multi-mode gel filtration and cation-exchange chromatography, are also effective to separate organic Te metabolites. 23 As mentioned above, the advantage of utilizing a gel filtration column is that the separation conditions are similar to the physiological conditions. In addition, the column does not require the addition of chelators, such as EDTA, tartaric acid, and phthalic acid, to achieve good separation of Te and Sb species in biological matrices.…”
Section: ·2 Speciation and Hyphenated Techniquesmentioning
confidence: 99%
“…[41][42][43] Recently, the major urinary Te metabolite in rat, an experimental animal, was identified by HPLC-ICP-MS and ESI-MS-MS after tellurite, an inorganic Te compound, was ingested. 23 The Te metabolite was trimethyltelluronium (TMTe). However, no peaks corresponding to Te-containing sugars, i.e., tellurosugars, were detected on HPLC-ICP-MS equipped with a gel filtration column or a cation-exchange column.…”
Section: ·2 Metabolism Of Tellurium Based On the Characterizationmentioning
confidence: 99%